On the Origin of Hydrocarbons in the Main Lower Pliocene Reservoirs of the South Caspian Basin, Azerbaijan. Issue 1 (February 2015) - Feyzullayev, A.A.; Tagiyev, M.F.; Lerche, I.
Two opposing points of view concerning the sources of hydrocarbons (HC) in the main reservoirs of the South Caspian Basin (SCB) Productive Series (PS-Lower Pliocene) reflect syngenetic or epigenetic genesis. Based on recent research results the nature of HCs in the PS is shown to be epigenetic. In the elevated onshore parts of the SCB PS Oligocene-Lower Miocene (Maikop series) rocks play a prevailing role in the formation of oil fields but in the central buried part of the SCB Middle-Upper Miocene rocks (Diatom suite) play a more dominant generation role. Hydrocarbon generation induces overpressure as shown by direct measurements in wells. The formation of HC pools in the PS occurred as a consequence of subvertical migration from underlying Oligocene-Miocene deposits, characterized by impulsive injection. Two main phases of oil migration occurred during the development of commercial accumulations in the PS. The distance of subvertical migration of HCs in the SCB is estimated to be about 4 km for oils and 10–11 km for gases.